Forward Position Analysis of 3-RPS Parallel Mechanism based on ADE-Newton algorithm - Peng Siyang; Li Ping; Che Linxian; Du Li (Jixie chuandong)
By a combination of the intelligent optimization algorithm and the numerical iteration method,a combined algorithm called Adaptive differential evolution and Newton iteration（ ADE-Newton） algorithm is constructed. Taking 3-RPS parallel mechanism for research object and the principle and steps of using ADE-Newton algorithm to solve the forward position of parallel mechanism are expounded in detail. In order to verify effectiveness and generality of ADE-Newton algorithm,the numerical examples of the forward position of different length of driving shaft length are given. The results show that ADE-Newton algorithm can obtain all high accuracy solutions in condition of different length of driving shaft with higher efficiency and lighter computational cost. And the performances of artificial bee colony,particle swarm optimization and differential evolution algorithms in solving forward position of 3-RPS parallel mechanism is compared. The results show that the computational efficiency,accuracy robustness and reliability of the ADE-Newton algorithm are higher than those of the contrast algorithm.